2001
DOI: 10.1038/88850
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Caenorhabditis elegans longevity protein DAF-16 by insulin/IGF-1 and germline signaling

Abstract: The lifespan of Caenorhabditis elegans is regulated by the insulin/insulin-like growth factor (IGF)-1 receptor homolog DAF-2, which signals through a conserved phosphatidylinositol 3-kinase (PI 3-kinase)/Akt pathway. Mutants in this pathway remain youthful and active much longer than normal animals and can live more than twice as long. This lifespan extension requires DAF-16, a forkhead/winged-helix transcription factor. DAF-16 is thought to be the main target of the DAF-2 pathway. Insulin/IGF-1 signaling is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

59
924
1
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 944 publications
(989 citation statements)
references
References 30 publications
59
924
1
5
Order By: Relevance
“…Nuclear translocation of DAF-16 increases transcription of stress-response genes 18 . To determine whether the lifespan extension attributable to long telomeres is relevant to the daf-16 signaling pathway, we examined the lifespan of daf-16 worms with long telomeres (F25-2 progeny) and found that it was not longer than that of control daf-16 mutant worms (Fig.…”
mentioning
confidence: 99%
“…Nuclear translocation of DAF-16 increases transcription of stress-response genes 18 . To determine whether the lifespan extension attributable to long telomeres is relevant to the daf-16 signaling pathway, we examined the lifespan of daf-16 worms with long telomeres (F25-2 progeny) and found that it was not longer than that of control daf-16 mutant worms (Fig.…”
mentioning
confidence: 99%
“…In mammals, this subfamily is involved in a wide range of crucial cellular processes regulating stress resistance, metabolism, cell cycle arrest, and apoptosis, but their role in longevity still remains to be elucidated. FOXO proteins function mainly as transcriptional activators by binding the consensus core recognition motif TTGTTTAC, and their activity is inhibited by the IIS pathway (Biggs et al ., 1999; Brunet et al ., 1999; Henderson & Johnson, 2001; Lin et al ., 2001; Calnan & Brunet, 2008; Zanella et al ., 2010; Webb & Brunet, 2014). Briefly, insulin or IGF‐1 triggers an intracellular pathway mediated by PI3K‐AKT, allowing phosphorylation of FOXO factors by the serine/threonine kinase AKT at three conserved residues within the FOXO proteins.…”
Section: Foxo Transcription Factorsmentioning
confidence: 99%
“…This lifespan extension caused by DAF‐2 mutations required the activity of DAF‐16, which encodes the single FoxO homolog in C. elegans (Kenyon et al ., 1993; Lin et al ., 1997; Ogg et al ., 1997). DAF‐16 is inactivated via its nuclear export by the evolutionary conserved signaling pathway downstream of DAF‐2 receptor (Henderson & Johnson, 2001; Lee et al ., 2001; Lin et al ., 2001). HSF‐1, the C. elegans heat‐shock transcription factor, is also required in DAF‐2 mutants to extend lifespan.…”
Section: Animal Modelsmentioning
confidence: 99%
“…This signal depends on the presence of a functioning insulin receptor (encoded by a wildtype allele of daf-2), an insulin signaling nuclear hormone receptor (daf-12) and a functional daf-16, which is the downstream transcription factor controlled by the insulin signaling cascade [71] (Box 1). In other words, the negative effect of signals from the reproductive system depends on a functional insulin signaling pathway, which is known to regulate many aspects of metabolism.…”
Section: Box 2 Reproductive System Signals That Affect the Life Spanmentioning
confidence: 99%